Look-at-the-air João and Unquiet Felipe: attention riots and hyperactivity - Florindo Stella (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The structure of the cognitive processes, from the relations between the citizen and the enviroment, constitutes the learning base. Amongst the diverse cognitive processes, the attention represents an essential mechanism for the understanding and incorporation of new contents. Riots of the attention process, besides compromising the learning, are extended for hyperactivity behaviors. The attention riots and the hyperactivity - intimately correlated phenomena - contribute to the significant difficulties the citizen has in other cognitive functions, as language, calculation, capacity of recognition and planning, ability of behaviors self-correction, etc. The teacher's pedagogical performance, integrated to the interdisciplinary action of other qualified professionals and family, constitutes a promising strategy in the boarding and orientation of the child with attention riots and hyperactivity.